2012
DOI: 10.1515/bmt-2012-0012
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of pull-out strength of cement-augmented pedicle screws with CT-volumetric measurement of cement

Abstract: Compared with the control, a cement volume between 2.0 and 3.0 ml increased the pull-out strength significantly and is relevant for clinical purposes, whereas a volume of 0.5 ml did not. A cement volume beyond 3.0 ml should further increase the pull-out strength because the correlation was linear at least up to 4.0 ml, but the possibility of in vivo cement leakage with increasing volume has to be considered. Pressure-controlled cement application might be a tool to avoid this complication. The cement almost co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 38 publications
0
23
0
1
Order By: Relevance
“…The exact cement volume injected intra-operatively is triggered by fluoroscopy, showing its distribution around the screw. A clear mechanical advantage of increased pullout strength of high viscosity cements was not found in vitro [25].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The exact cement volume injected intra-operatively is triggered by fluoroscopy, showing its distribution around the screw. A clear mechanical advantage of increased pullout strength of high viscosity cements was not found in vitro [25].…”
Section: Discussionmentioning
confidence: 90%
“…A finite element analysis showed that volumes between 2 and 3 ml increased pullout resistance significantly compared to non-augmented screws, and volumes between 3 and 4 ml could theoretically further increase pullout strength [25]. In vitro, the realization of a balloon kyphoplasty, which concentrates a higher cement volume around the screw, did not increase pullout resistance in comparison to a fenestrated screw augmentation [4].…”
Section: Discussionmentioning
confidence: 95%
“…2,45 The cement volume should be kept to the smallest volume needed and should not exceed 2.8 ml per pedicle screw. 17 High application pressure, liquidity of the cement, and special anatomical features of the perivertebral venous system are conducive to cement leakage.…”
Section: 4%mentioning
confidence: 99%
“…According to the literature, 17% of revision surgeries are associated with pedicle screw failure [5]. Thus, CAPSI has been widely used for patients with poor bone quality due to its reliable biomechanical stability [15,[24][25][26]. But the treatment of multilevel LDD with cement-augmented pedicle screws is more complicated and challenging compared with 1 or 2-level LDD because of the increase of CL and mechanical overload [27].…”
Section: Discussionmentioning
confidence: 99%